2016
DOI: 10.1021/acs.chemmater.6b02885
|View full text |Cite
|
Sign up to set email alerts
|

Guidelines for Tailored Chemical Functionalization of Graphene

Abstract: Graphene oxide (GO) has been synthesized by the Hummers method with modification of experimental condition by different research groups, but there is no guideline to prepare tailored GO for targeted applications. In this research, we suggest a guideline for tailor-fittable functionalization of graphene on the basis of the scope of our previous report on the two-step oxidation of GO. We describe a detailed procedure for synthesis of GO, effects of degree of step I oxidation on characteristics of GO and comparin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(15 citation statements)
references
References 38 publications
0
15
0
Order By: Relevance
“…Chong Rae Park et al has provided us guidelines to prepare tailored GO for targeted applications. 7 In 2003, Deḱańy et al reported modified GOs by grafting primary aliphatic amines and amino acids onto its surface. 8 Since then, many researchers have tried different methods to realize the modification of GO, and the fGOs show great potential applications.…”
Section: Introductionmentioning
confidence: 99%
“…Chong Rae Park et al has provided us guidelines to prepare tailored GO for targeted applications. 7 In 2003, Deḱańy et al reported modified GOs by grafting primary aliphatic amines and amino acids onto its surface. 8 Since then, many researchers have tried different methods to realize the modification of GO, and the fGOs show great potential applications.…”
Section: Introductionmentioning
confidence: 99%
“…The addition of water (previously identified as the second oxidation step in CGO synthesis)27,28 served as the important factor in the formation of structural defects. In the preparation of GO-20 and GO-5, this step was skipped by terminating the reaction in excess water at room temperature (Experimental section).…”
Section: Resultsmentioning
confidence: 99%
“…The final product, with a bright yellow appearance, was found to be highly dispersible in water, with a defect-rich nanostructure 26. However, over-oxidation in the second step of functionalization27,28 results in the formation of unrepairable structural defects that severely deteriorate the material performance of the reduced GO (rGO). Modifications to the traditional recipe have been reported continuously 2932.…”
Section: Introductionmentioning
confidence: 99%
“…All chemicals were used without further purification. EOG and GO were synthesized based on our previously reported methods [3,4,21] and prepared as colloidal suspensions with various concentrations (up to 12 mg/mL). The size of the EOG and GO was 2.5 um and 25 μm, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…The ultrahigh tensile strength (~130 GPa) and Young’s modulus (~1 TPa) of graphene [1] make it an excellent nanofiller to enhance the mechanical properties of composites [2]; however, its poor dispersibility prevents the preparation of high-strength composites. Thus, graphene oxide (GO) can be used as an alternative because of the high dispersibility induced by its oxygen functional groups, including hydroxyl, epoxide, and carboxyl groups [2,3,4,5]. Indeed, GO has improved the mechanical properties of epoxy [6], poly(L-lactic acid) [7], polycarbonate [8], and polyimide [9,10].…”
Section: Introductionmentioning
confidence: 99%